Treatment of Anemia of Chronic Disease with True Iron Deficiency in Pregnancy. (4th December 2017) - Amstad Bencaiova, Gabriela; Krafft, Alexander; Zimmermann, Roland; Burkhardt, Tilo
Abstract : Objective. We assess and compare the efficacy of anemia treatment in pregnant women with anemia of chronic disease with true iron deficiency and in women with iron deficiency anemia. Study Design. Fifty patients with moderate anemia (hemoglobin 8.0–9.9 g/dl) and iron deficiency (ferritin < 15 μ g/l) were treated in the Anemia Clinic at the Department of Obstetrics. Results. All patients showed stimulation of erythropoiesis as evidenced by an increase in reticulocyte count at day eight of therapy and showed an increase in hemoglobin and hematocrit at the end of therapy (p < 0.00 1 ). The target hemoglobin (≥10.5 g/dl) was achieved in 45/50 women (90%). 12 patients showed anemia of chronic disease with true iron deficiency (12/50; 24%). Seven women (7/12; 59%) with anemia of chronic disease and iron deficiency responded well to anemia treatment. 50% of women with anemia of chronic disease and iron deficiency (3/6) responded well to intravenous iron, and 67% (4/6) responded well to the combination of intravenous iron and recombinant human erythropoietin. Conclusion. Because of frequent true iron deficiency in pregnant women with anemia of chronic disease, anemia of chronic disease in pregnancy is often falsely diagnosed as iron deficiency anemia.